Anti-proliferative effect of main dietary phytosterols and β-cryptoxanthin alone or combined in human colon cancer Caco-2 cells through cytosolic Ca+2 – and oxidative stress-induced apoptosis. (January 2015) - Cilla, Antonio; Attanzio, Alessandro; Barberá, Reyes; Tesoriere, Luisa; Livrea, Maria A.
Highlights: β-cryptoxanthin and main dietary phytosterols decrease Caco-2 cell proliferation. Apoptotic effect performed at compatible physiological human serum levels. Intracellular Ca 2+ influx and increase of ROS levels as initial apoptosis triggers. No additive or synergistic effects have been observed in their action. Antiproliferation complements their cardiovascular and osteoporosis decreasing risk. Abstract: β-cryptoxanthin (β-Cx) and phytosterols (Ps) have potential against different cancer types, including colon cancer. However, their combined action has not been reported so far. Human colon cancer Caco-2 cells were treated 24 h with β-Cx and/or main dietary Ps (β-sitosterol, campesterol and stigmasterol), alone or in combination, at concentrations compatible with physiological human serum levels. A decrease in cell viability due to apoptosis (rise in sub-G1 population and exposure of membrane phosphatidylserine) was accompanied with dephosphorylation of BAD, mitochondrial depolarization and caspase 3-dependent PARP cleavage, with intracellular Ca 2+ influx and increase of RONS levels as initial triggers. Ps and β-Cx, alone or in combination showed anti-proliferative activity against human colon adenocarcinoma Caco-2 cells through the mitochondrial pathway of apoptosis. No additive or synergistic effects were observed. The importance of bioactivity-guided assays with mixtures of dietary bioactive compounds to determine their eventual interactions in the functional food context is demonstrated.